Effect of Geogrid Layers on Seismic Behavior of Stone Columns - A. Moazzami (Iranica Journal of Energy and Environment)
The purpose of this research is to investigate the effect of geogrid layers on the seismic behavior of stone columns. In this article, it has been addressed by both manual and numerical methods. In addition, the seismic behavior of stone columns covered with geogrid was investigated. By using numerical modeling and finite element method and by using two-dimensional Plexis software, the seismic behavior of stone columns with geogrid covering in the near and far field compared to normal stone columns was evaluated. The results show that the bearing capacity of a stone column increases with the use of a geogrid cover, and the smaller the diameter of a normal stone column or one with a geogrid cover, the lower the load capacity in a static state, and the use of a geogrid cover increases the bearing capacity of a stone column. In the case of plate loading, the smaller the diameter of the normal or geogrid-covered stone column is, the less load-bearing capacity it has in static mode, and the use of geogrid cover increases the load-bearing capacity of the stone column. Based on the results of numerical analysis, geogrid reduces the lateral deformation and displacement of stone columns during an earthquake. By examining different types of geogrid with different hardness, it was found that the type of geogrid had no effect on the seismic behavior of the stone column. Also, covering the upper half of the stone column with geogrid was enough to improve the seismic behavior of the stone column, and of course, this work is also economical.